(untitled) (Materiali di Estetica. Terza serie, 2017)
The author illustrates some essays by Gillo Dorfles, in which the Italian philosopher of Aesthetics recovers Giambattista Vico’s studies on metaphor, highlighting not only its rhetorical and linguistic value, but also its cognitive and theoretical value, not conceived as a simple aesthetic embellishment, but as a semiotic tool able to convey new epistemic contributions.